1996
DOI: 10.1111/j.1399-0039.1996.tb02520.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA typing of the HLA‐A gene: population study and identification of four new alleles in Japanese

Abstract: With the use of polymerase chain reaction (PCR) and sequence-specific oligonucleotide probe (SSOP), we established a DNA typing method of the HLA-A locus. A pair of primers to amplify the highly polymorphic region of HLA-A gene including exon 2 and exon 3 was designed and the amplified DNAs were hybridized with 91 types of 32P labeled SSOPs. This method allowed discrimination of all known HLA-A alleles except for two combinations, A*0201 or A*0209 and A*0207 or A*0215N, which have identical sequences in exon 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 28 publications
3
93
0
Order By: Relevance
“…25,35 This information and the absence of HLA-A*0206 in general Caucasian populations might be the reasons why this allele has not been focused on until now. Because HLA-A*0206 is the second or third most common HLA-A2 subtype worldwide (unpublished data from the 12th IHW 13 ), the opportunity to utilize HA-1 H mHA for immunotherapy has been nearly doubled in eastern Asian populations. We found that 4B1-CTL failed to recognize LCL from an HA-1 H -positive individual expressing HLA-A*0207 (another allele frequently expressed in the Asian population).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,35 This information and the absence of HLA-A*0206 in general Caucasian populations might be the reasons why this allele has not been focused on until now. Because HLA-A*0206 is the second or third most common HLA-A2 subtype worldwide (unpublished data from the 12th IHW 13 ), the opportunity to utilize HA-1 H mHA for immunotherapy has been nearly doubled in eastern Asian populations. We found that 4B1-CTL failed to recognize LCL from an HA-1 H -positive individual expressing HLA-A*0207 (another allele frequently expressed in the Asian population).…”
Section: Discussionmentioning
confidence: 99%
“…The next most common HLA-A2 subtypes appear to be HLA-A*0206 and/or -A*0207, which are found frequently in the eastern Asian populations, including Chinese and Japanese populations. 13,14 To date, it has not been examined whether an HLA-A*0201-restricted HA-1 H mHA epitope can be presented by HLA-A*0206, which possesses a single amino-acid substitution (9Phe-9Tyr) in the B-pocket compared with HLA-A*0201, 15 probably owing to the rarity of the HLA-A*0206 allele in Caucasian populations. While attempting to identify HLA alleles capable of presenting HA-1 mHAs other than the previously reported HLA-A*0201 and HLA-B60, 5 we unexpectedly found that HLA-A*0206 was able to present the nonameric peptide originally described as the A*0201-restricted HA-1 H mHA (VLHDDLLEA).…”
Section: Introductionmentioning
confidence: 99%
“…HLA-A24 is one of the most popular HLA allele in Japanese ( > 60%) and also in Caucasian (Kubo et al, 1994;Kondo et al, 1995;Date et al, 1996). Moreover, most of their microallele consist of HLA-A*2402.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we have newly identified an epitope peptide of HER2 / neu restricted by HLA-A24, one of the most common alleles in Japanese and Caucasians (Kubo et al, 1994;Kondo et al, 1995;Date et al, 1996). And the CTLs induced by peptide-pulsed autologous DCs specifically killed HLA-A24-positive and HER2 / neu-overexpressing colorectal carcinoma cell lines.…”
mentioning
confidence: 99%
“…2 (Medical & Biological Laboratories, Nagoya, Japan), as described previously. 9 HLA genotyping data from 678 healthy Japanese controls selected at random were obtained for HLA-A and -DRB1 by the PCR-SSOP-based typing method as described previously 10,11 and for HLA-B using PCR-reverse SSOP-based RELI SSOP HLA-B typing kits (Invitrogen, Carlsbad, CA, USA).…”
Section: Hla Genotypingmentioning
confidence: 99%